Plan de negocios para la elaboración artesanal y comercialización de un snack de cacao blanco orgánico en la ciudad de Quito - Rueda Manosalvas, Katheryn Yanara (2020)
The objective of this business plan is to prepare and commercialize a snack based on organic white cocoa, which will be distributed through biodegradable packaging, making it friendly to the environment, thus improving the reduction of plastic contamination. This product allows its consumers to enjoy a meal high in components good for health, perfecting their habitual consumption, it can be found in large supermarket chains in the city of Quito. To determine its feasibility, a correct analysis of external factors was carried out using tools such as PEST and PORTER, where it was evident that its threats in the sector can be countered with the opportunities found in it. Through the client's analysis of qualitative and quantitative data, it was possible to determine characteristics of the client's target market, such as the tastes and preferences regarding the product to be made, forming a market opportunity with the analysis of the environment. Based on the information obtained from the previously mentioned analyzes, the marketing plan for the selected market segment establishes certain characteristics relevant to the product, price, place and promotion. After this the guidelines of the organizational structure of the company are established. Finally, the financial analysis is developed, which details the income, costs, expenses and financial indicators, in order to demonstrate the success and viability of the project during the five-year period.